(untitled) (Research, Society and Development, 2021)
The objective of the study was to evaluate the oral condition of patients in the Intensive Care Center (ICU) of a hospital in the city of Belo Horizonte, Minas Gerais. This is a cross-sectional, retrospective and descriptive epidemiological study of medical records. 112 medical records were evaluated between January and December 2015. Most patients were men (53.57%), between the 5th and 6th decades of life (25.89%). Older patients, between the 5th and the 9th decade of life, had a longer stay in the ICU. Cases of pneumonia infection were observed in 40 patients (35.71%), which also correlated with the appearance of changes in the oral mucosa. Nosocomial pneumonia was found in 16 patients (14.28%), nine of which were partially edentulous (56.25%). When the historical series on the incidence of pneumonia associated with mechanical ventilation (VAP) was analyzed in this hospital, there was a reduction of 54.9% comparing the year 2005, the year of introduction of the hospital dentistry service, to the year 2015. This study suggests that changes in the oral cavity may be related to nosocomial infections, such as pneumonia, and even though the presence of the dentist positively impacts the patient’s general health.